2023
DOI: 10.17221/55/2023-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioengineering treatments on reduction of soil erosion from road cut slope and fill slope

Aidin Parsakhoo,
Seyed Ataollah Hosseini

Abstract: The efficiency of different conservation practices on soil loss from road side slopes is scarcely identified in the Hyrcanian forests of Iran, which could retard the implementation of these management practices. Sediment of 48 plots on the cut slopes and fill slopes of forest roads were collected to explore their responses to soil conservation practices, including straw bale (SB), living hedge (LH), dead hedge (DH), geo-cell (GC), geotextile (GT), and bare soil (BS). Moreover, the efficiency of conservation pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Therefore, when managing and regulating forest roads, priority should be given to biological measures. Additionally, studies have shown that a combination of engineering measures and biological measures can achieve better effectiveness in mitigating road erosion and the transport of road-eroded sediment [117], but the economic benefits are not yet clear.…”
Section: Regulation Of Forest Road Erosion and Sediment Transportmentioning
confidence: 99%
“…Therefore, when managing and regulating forest roads, priority should be given to biological measures. Additionally, studies have shown that a combination of engineering measures and biological measures can achieve better effectiveness in mitigating road erosion and the transport of road-eroded sediment [117], but the economic benefits are not yet clear.…”
Section: Regulation Of Forest Road Erosion and Sediment Transportmentioning
confidence: 99%